Reversibly thermochromic and high strength core‐shell nanofibers fabricated by melt coaxial electrospinning. Issue 21 (16th January 2021) - Wang, Shuoshuo; Yi, Liqiang; Fang, Yini; Wang, Lina; Yao, Juming; Marek, Jaromir; Zhang, Ming
Abstract: Recent years, phase change materials (PCMs) with potential to store and transform energy have attracted broad attention, especially in the field of thermal energy storage. However, the instability and leak proneness of PCMs limit their universal application. In this paper, core‐shell fibers with 1‐tetradecanol (TD) as core and poly(vinylidene fluoride) (PVDF) as shell were prepared via melt coaxial electrospinning method, and for improvement, the dye composed of crystal violet lactone (CVL) and bisphenol A (BPA) was added to the core to endow the fiber the function of reversible thermochromism. During the preparation process, it was found that the addition of NaCl could regulate the fiber morphology and strength its mechanical property. By adjusting the concentration of shell solution and the flow rate of core solution, the high‐strength reversible thermochromic fibers were produced when polymer concentration was 24 wt% with a core feed rate of 0.4 ml/h. The latent heat of these fibers is up to 88.71 J/g. Besides, its color can change from blue to white when heated, and the transition temperature is around 38°C. And 100 thermal cycle tests of the fiber showed its strong thermal stability and thermochromic property. Abstract : In this paper, a high‐strength reversible thermochromic fiber was prepared by the melt coaxial electrospinning method. Adding NaCl to the shell solution to enhance conductivity improves the morphology of the fibers. And the strength of them has also been greatly improved. The fibers have high latent heat and good reversible thermochromic performance, so it has huge potential applications in thermal response sensors and protective clothing. This work provides a strong support for the research and development of functional fibers.